Analyzing the Testing Ways of Milk and Milk Products (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2024)
In the given article the testing analysis of milk products, identifying the acid of milk and using the several ways on GOST standard as well ; our aim is to research the milk products and on the gained results to give the new code numbers